Islamic entrepreneurship: analysis of research trend - Siti Haslina Md Harizan; Mohd Saifulamri Mustafa (Penerbit Universiti Kebangsaan Malaysia, 2020)
Entrepreneurship has been an endeavour carried out by people who are industry players and whom have good intentions in achieving concrete socio-economic development leading to prosperity for the general populace. In Islam, entrepreneurship is meant not only for fulfilling on material individuals needs, society and the country, but is also as a way of worship. The growth of the Muslim population around the world has somehow paved a way for more Muslim entrepreneurs to get involved in entrepreneurship activities in responding towards the current market as well as abiding with the religious teachings. To date, studies have hardly looked into the research trends pertaining to Islamic entrepreneurship. Hence, it is the attempt of the present study to provide some insights regarding the focus of research, the trends and the gaps to be filled by future researchers. Guided by the PRISMA Statement research method, a systematic review of scientific databases and manual search on established sources identified 84 related studies based on five properties namely types of paper, countries of studies, research design, research topics, and overall research trends. Findings revealed that most of papers are original studies, conducted in Malaysia, and being exploratory in nature. Four themes and fourteen sub-themes related to Islamic entrepreneurship were identified, comprising organizational characteristics (6 sub-themes), entrepreneurs’ traits (4 sub-themes), enterprise support system (2 sub-themes), and external forces (4 sub-themes). Overall, no topic has yet to approach the saturation level in research. This study may guide future researchers in expanding their researches in Islamic entrepreneurship.